Potential of three different lactic acid Bacteria to use as starter culture for production of type II sourdough breadmaking - Gül, Latife Betül; Gül, Osman; Çon, Ahmet Hilmi (Springer Science and Business Media LLC, 2022)
The principle objective of this study was to investigate the use of three different lactic acid bacteria (Lactobacillus curvatus N19, Weissella cibaria N9 and L. brevis ED25) lyophilized with optimum cryoprotective agent formulations as Type II sourdough culture to develop sourdough bread in terms of physicochemical, textural and sensory characteristics as well as volatile aroma compounds. Compared to control sample (fermented only commercial yeast), specific volume, crust and crumb color, and textural properties were markedly more acceptable for sourdough bread. The concentration of lactic (2.12-2.87 g/kg) and acetic (0.43-0.77 g/kg) acids in the sourdough bread was significantly higher compared to control sample (0.28 and 0.09 g/kg, respectively). A total of 57 volatile compounds including 13 alcohols, 9 esters, 8 ketones, 13 aldehydes, 10 acid group components, and 4 other compounds (such as oxidation product amine, terpene, sulfur compounds, organic compounds) were detected. Among these compounds, alcohols and aldehydes were significantly higher in control sample, while the ratio of acids was found to be higher in sourdough breads. The evaluation scores of the sourdough breads had desirable sensory features, but in terms of general acceptance values, it was concluded that those containing L. brevis ED25 was more preferred.
Keywords: 2. Zero hunger